How to Manage Complications Related to the Use of Intramedullary Screws in Metacarpal Fractures: Case Series - Camacho, Eliana; Craviotto, Matías; D'Oliveira, Lucía (Revista Iberoamericana de Cirugía de la Mano, 2021)
The use of intramedullary screws has been increasing among hand surgeons in cases of metacarpal fractures due to their low morbidity, and because they minimize incisions and dissection, and require less tissue manipulation and deperiostization. However, there are few published articles on the complications that arise from its use. Therefore, the purpose of the current study is to present a series of cases of complications following the use of intramedullary screws in metacarpal fractures that required surgical intervention, and to describe the surgical technique used to solve them .Methods We performed a retrospective multicenter study in which we reviewed the clinical history, surgical descriptions and radiographs of the patients submitted to fixation of intramedullary compression screws for metacarpal fractures. We defined as complications infection, lesion to the extensor apparatus, bending of the implant, loss of reduction, hardware failure, malrotation, and non-union.Results Out of a total of 45 patients, we reported 3 cases of complication: 1 patient with loss of reduction, and 2 patients with bending of the implant. In the three cases, the screw was removed without complications, and the focus of the fracture was stabilized.Conclusion Intramedullary fixation with compression screws is increasingly being used for metacarpal fractures, with reports of low rates of complications. In the series of cases herein reported, the complications were solved without difficulty, and the patients showed a good recovery in hand function in the follow-up. Knowledge of the possible complications and their management enables us to provide more safety to the patient at the time of choosing this technique.Los tornillos intramedulares son cada vez más utilizados por los cirujanos de mano en fracturas de metacarpianos dada su baja morbilidad, pues minimizan las incisiones, la disección, y requieren una menor manipulación de tendones y desperiostización. Sin embargo, son pocos los artículos publicados que se dedican a las complicaciones que surgen de su uso. Por lo tanto, el objetivo de este trabajo es presentar una serie de casos de complicaciones, ocurridas luego del uso de tornillos intramedulares en fracturas de metacarpianos, que requirieron una reintervención quirúrgica, así como describir la técnica utilizada para solucionar dichas complicaciones.Métodos Se realizó un estudio descriptivo, retrospectivo, multicéntrico, en que se revisaron las historias clínicas, descripciones operatorias y radiografías de los pacientes que se sometieron a enclavijado intramedular con tornillos compresivos para fracturas de metacarpianos. Definimos como complicaciones infección, lesión del aparato extensor, doblamiento del implante, pérdida de reducción, rotura del implante, malrotación, y no unión.Resultados Se reportaron 3 complicaciones de un total de 45 pacientes. Una de las complicaciones fue pérdida de reducción, y las otras dos, doblamiento del implante. En los tres pacientes se realizó retiro el tornillo sin complicaciones, y se estabilizó el foco de fractura.Conclusión El enclavijado endomedular con tornillos compresivos es cada vez más utilizado en fracturas de metacarpianos, y se reporta una baja tasa de complicaciones. En la serie de casos presentada, éstas fueron resueltas sin dificultades, y los pacientes lograron una buena función de la mano en el seguimiento postoperatorio. El conocimiento de las posibles complicaciones y su manejo permite brindar mayor seguridad al paciente a la hora de elegir esta técnica.
Keywords: metacarpal; fracture; intramedullary screw; complications